Evaluation of Antibiotic Use in Patients with Acute Appendicitis - Romauli Lumbantobing; Lidwindy Morani Logo Ule; Nur Nunu Prihantini (PT FORMOSA CENDEKIA GLOBAL, 2026)
This activity aims to evaluate the accuracy of antibiotic use among patients with acute appendicitis at Aeramo Regional General Hospital to support rational healthcare services. The process involved observing medical records from April 2024 to April 2025. The implementation method used a qualitative descriptive analysis based on Gyssens' criteria to assess indications, dosages, routes, and timing of administration in accordance with ASHP and IDSA guidelines. Evaluation results showed that 53% of antibiotic use was rational (Category 0), though inaccuracies in indications remained at 33%, particularly in non-perforation cases. Consequently, strengthening compliance with local clinical protocols is essential to prevent the risk of antimicrobial resistance within the hospital environment.